MENILIK RELASI NEGARA DAN AGAMA: ANALISIS LEGISLASI NEGARA TERKAIT PENDIDIKAN AGAMA - Mohamad Yusuf; Carl Sterkens (Institut Agama Islam Negeri Kendari, 2017)
This article aims to analyse the State’s laws regarding models of religious education, by evaluating Law No. 20/2003, concerning the national system of education and other related Laws. Two questions are highlighted: What type of religious education is favoured by the State? Does the preference for a certain type of religious education reflect a specific vision of the State-religion relationship? Our data consisted of two sources: the State’s law on religious education, focusing on Law No. 20/2003, and the minutes of the parliament meeting approving Law No. 20/2003. We found that Law No. 20/2003 expresses the preference of the government for a mono-religious model. Indonesia is categoreized as having preferred treatment for some religions or support for a particular religious tradition. This categorisation is confirmed by the results of our research findings indicated by the preferential treatment delivered by the State, and the State’s legislation and regulations on religion.